1984
DOI: 10.1080/00288330.1984.9516050
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary investigation on effects of fluctuating flows on invertebrates of the Hawea River, a large regulated river in New Zealand

Abstract: An experiment with flow changing at 3, 9, and 18 m 3 s -1 h -1 on consecutive days failed to produce any measurable effect on benthic invertebrates in the regulated Hawea River, New Zealand, but did result in increased numbers of drifting chironomid larvae, trichopteran larvae, and oligochaetes compared to days when flow was stable. Drift densities were at least as high on the day flow changed at 3 m 3 s -1 h -1 (minimum flow 15 m 3 s -1 , maximum flow 30 m 3 s -1 ) as on subsequent days when flow changed at 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1

Year Published

1987
1987
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 6 publications
2
26
1
Order By: Relevance
“…Chance and Craig (1986) also reported that Simuliidae larvae had a lower risk of being displaced by moderate flow changes because of their hydrodynamic and morphological adaptations to cling to the substrate, which is much less true for Hydropsychidae. Chironomidae drift densities increased with increased flow fluctuations in both wet and dry seasons, corroborating the results of Irvine and Henriques (1984) but differing from the results of Gislason (1985) and Troelstrup and Hergenrader (1990).…”
Section: Discussionsupporting
confidence: 55%
“…Chance and Craig (1986) also reported that Simuliidae larvae had a lower risk of being displaced by moderate flow changes because of their hydrodynamic and morphological adaptations to cling to the substrate, which is much less true for Hydropsychidae. Chironomidae drift densities increased with increased flow fluctuations in both wet and dry seasons, corroborating the results of Irvine and Henriques (1984) but differing from the results of Gislason (1985) and Troelstrup and Hergenrader (1990).…”
Section: Discussionsupporting
confidence: 55%
“…III.l, Elliott 1984b) field manipulations of, for example, discharge (Gore 1977, Irvine andHenriques 1984), woody debris (Angermeier and Karr 1984), or watershed vegetation (Gurtz and Wallace 1984) promise faster success than the "observe and wait strategy".…”
Section: Discussionmentioning
confidence: 99%
“…The lateral displacement of water is reduced in confined channels relative to unconfined channels (Badri et al, 1987), causing a high degree of scouring and the dislodgement and drifting of organisms (Irvine and Henriques, 1984;Imbert and Perry, 2000). Lytle (2000) suggested many of these drifting organisms are delivered downstream, although many others may accumulate in slow flow areas, or shorelines (Winterbottom et al, 1997).…”
Section: General Response Patternsmentioning
confidence: 99%